Implementasi Akuntansi Berbasis Akrual Pada Pemerintah Daerah (Studi Pada Pemerintah Kota Semarang dan Pemerintah Kota Bandar Lampung) - Maryati, Ulfi; Yentifa, Armel; Andriani, Wiwik (Akuntansi dan Manajemen, 2015)
The aim of this research is to evaluate implementation of Accrual based accounting of local government in Kota Semarang and Kota Bandar Lampung. The research finds that Government Act (PP) No. 71 Year 2010 as amendment of Section 36 ayat (1) Regulation No 17-2003 and Pasal 70 section (2) Regulation No.1-2004 has instructed government to apply Accrual accounting by the year 2008. However, the regulation for implementing this Accrual based accounting has just established since 2010 in PP 71-2010. The establishment of this governmental act, all governments both local and central, must apply Accrual based accounting by the year of 2015. The years from 2010 until 2014 can be identified as the transition from cash based accounting to Accrual based accounting. In December 2013, Central government has set Regulation of Internal Affairs Ministry (Permendagri) No. 64 in 2013 which can be identified as the regulation for controlling the implementation of PP 71 in 2010 at local governments. Local government of Kota Semarang is the only region in Indonesia which has applied Accrual based accounting since 2008. In 2013, government of Bandar Lampung start implementing this financial policy informally, but actually they still use PP 24-2005. This research was conducted using qualitative research methods with library research technique. The result of implementation accrual accounting in two public governments is appropriated to conceptual framework.